Evaluating the Integration of Technical and Language Learning through CLIL-Based Cross-Curricular Writing for Marine Engineering Cadets - Kumar, P.Kamalesh; .Vairavan, C (Journal of Neonatal Surgery, 2025)
In the paper examines the effect of cross-curricular writing activities in a CLIL programme on the writing skill of the marine engineering cadets. A quasi experimental design was used with 60 second-year cadets in a maritime academy over a 12-week semester. The experimental group participated in CLIL-based technical writing tasks, such as the “Incident Report Simulation,” in which domain-specific content was combined with guided language learning. Pre- and post- tests were used to evaluate the change in writing competence and questionnaires as well as semi-structured interviews were employed to elicit qualitative data. Quantitative analysis showed a statistically significant improvement of 21.2 points (42.34%) in writing score, and supported increasing use of vocabulary, structural clarity and technical accuracy. The qualitative findings showed enhanced technical understanding, increased confidence in writing as well as high levels of engagement with digital instruments and peer feedback. Although there are challenges in reconciling technical precision and linguistic coherence in the process, the results support the educational value of CLIL-based cross-curricular writing as a pedagogical tool for reinforcing both technical and communicative skills in maritime academies.